Lower Serum Uric Acid Is Associated With Post-Stroke Depression at Discharge - Li, Guo; Miao, Jinfeng; Sun, Wenzhe; Song, Xiaoyan; Lan, Yan; Zhao, Xin; Qiu, Xiuli; Zhang, Chenyan; Zhu, Zhou; Zhu, Suiqiang (Frontiers in Psychiatry, 2020)
Background Serum uric acid (SUA) has been shown to play an important role in the pathophysiology of mood disorders including 3- and 6-month post-stroke depression (PSD). This study aimed to investigate whether SUA levels on admission were associated with PSD at discharge. Methods A total of 498 stroke patients were consecutively recruited from Tongji Hospital. Clinical and laboratory test data were collected on admission. They were categorized into equal tertiles according to the distribution of SUA and the number of patients. PSD status was evaluated by DSM-V criteria and 17-item Hamilton Rating Scale for Depression (HRSD) at discharge. Results The optimal cut-off points of SUA were: (T1) 80.00~300.80 umo1/L, (T2) 300.81~391.67 umo1/L, (T3) 391.68~710.0 umo1/L. A total of 232 patients (46.59%) were diagnosed as PSD at discharge. Significant differences were found between the PSD and non-PSD groups in SUA tertiles of patients (P = 0.00). After adjustment for conventional confounding factors, the odds ratios of PSD were 5.777 (95%CI, 3.463~9.637, P=0.00) for the lowest tertile and 4.153 (95%CI, 2.492~6.921, P = 0.00) for the middle tertile of SUA, as compared with the highest tertile. In restricted cubic spline (RCS) regression, continuous SUA showed linear relation with PSD risk at discharge after 300 umol/L. Conclusions Lower SUA levels on admission were found to be associated with PSD at discharge and the threshold effect was also revealed. For stroke patients, doctors should pay attention to the baseline SUA for screening high-risk PSD at discharge in clinical practice.